Pengembangan Media Pembelajaran Powerpoint Interaktif Materi Jenis-Jenis Pekerjaan di SD Kelas IV - Geby Ramdani; Erwin Rahayu Saputra (Jurnal Sekolah Dasar, 2023)
The lack of use of learning media can be an inhibiting factor in the teaching and learning process as a result of which learning is not optimal. In order to overcome this, it is necessary to develop learning media. One of the learning media that can overcome this is powerpoint media, powerpoint media is a learning media that was developed to increase students' understanding and interest in social studies subjects. Therefore the authors conducted research. This research is seen as development research which aims to develop powerpoint learning media as social studies learning media for class IV at SD Negeri 1 Parakannyasag. The type of research used in this research is a qualitative model. For data collection techniques used are validity and observation. Powerpoint media was developed by implementing it directly based on the Analyze, Design, Development, Implementation, Evaluation (ADDIE) procedure. The results of the validity of the material experts and media experts after implementing them at SD Negeri 1 Parakannyasag obtained a percentage of 95% for material experts and 89.2% for media experts so that they can be categorized as valid. Based on the results of research and development, it can be concluded that powerpoint media in social studies class IV material for types of work in elementary schools is appropriate for use in learning.